(untitled) (Asian Journal of Medical and Biological Research, 2016)
Formaldehyde (FA) is toxic over a range of doses and of particular concern to anatomists and medical students on laboratory use. FA induces several characteristics of neurotoxicity in addition to systemic effects. Therefore, to know the toxic effects of FA on brain and lungs, mice were collected from international center for diarrheal disease research. They were divided into four groups i.e. control, inhalation, oral and intraperitoneal. The inhalation, oral and intraperitoneal exposure groups further divided into three subgroups which were subjected to exposure of FA daily for 30 days in case of inhalation and oral groups and 10 days in intraperitoneal group for acute toxic effects. Morphological study showed gross abnormalities i.e. congestion on lungs. But no gross abnormal features observed on brain. In 5 ppm treated inhaled group, lungs tissue revealed hemorrhages. In the inhaled groups, brain tissue showed degenerating neurons with either pyknotic or karyorrhectic nuclei are gradually increased in highest concentration group. These data supports the view that FA has adverse effects on the morphology of brain and lungs. Asian J. Med. Biol. Res. June 2016, 2(2): 229-235